Inequality and happiness: when perceived social mobility and economic reality do not match - Bjørnskov, Christian; Dreher, Axel; Fischer, Justina A. V.; Schnellenbach, Jan (CESifo working papers, 2010)
In this paper, we revisit the association between happiness and inequality. We argue that the interaction between the perceived and the actual fairness of the income generation process affects this association. Building on a simple model of individual labor-market participation under uncertainty, we predict that higher levels of perceived fairness cause higher levels of utility, and lower preferred levels of income redistribution. In societies with a low level of actual social mobility, income inequality is perceived more negatively with increased perceived fairness, due to the need for unexpected policy changes as a response to many unsuccessful investments of overly optimistic individuals. This effect becomes smaller as actual social mobility increases. Using data on happiness and a broad set of fairness measures from the World Values Survey, we find strong support for the negative (positive) association between fairness perceptions and the demand for more equal incomes (subjective wellbeing). We also find strong empirical support for the disappointment effect in countries with low social mobility. Consistent with our theoretical model, the results for high-mobility countries turn out to be ambiguous. -- happiness ; life satisfaction ; subjective well-being ; inequality ; income distribution ; redistribution ; political ideology ; justice ; fairness ; World Values Survey
Parallel als Druckausg. erschienen
Keywords: Arbeitspapier; Graue Literatur